The Effect of Guided Inquiry Learning Model on Chemistry Learning Outcomes - Siti Hasanah; Agus Abhi Purwoko; Aliefman Hakim (Journal of Science and Science Education, 2020)
Teachers and students still dominate the learning process at SMAN 1 Lingsar are even less active. This study aimed to determine the effect of the Guided Inquiry learning model on students' chemistry learning outcomes. This study used quasi-experimental research (quasi-experimental) with a nonequivalent control group design pre-test-post-test design. The population in this study were all Class XI IPA SMAN 1 Lingsar. The sampling technique used a quota sampling technique. The sample consisted of 2 classes, namely class XI MIA 1 as the experimental class and class XI MIA 4 as the control class. The instruments in this study were 3, namely: RPP, LKPD, and Tests. The test is carried out at the beginning of the meeting (pre-test) and the end of the session (posttest). The resulting data were tested using the ANCOVA test. The results showed differences in chemistry learning outcomes for students who took the guided inquiry learning model with those who took the conventional learning model. The results of statistical tests obtained a significance value of the learning model of 0.011. So because the amount of the Sig value is less than 0.05, H0 is rejected. It means a linear relationship between them with the average chemistry learning outcomes in the class that received the guided inquiry empowerment model higher than the control group. Furthermore, the covariance proved also to support the improvement of students' chemistry learning outcomes with a significance level of 0.000. It means that there is a linear relationship between the covariance and the dependent variable